DETERMINAN DEPOSITO VALUTA ASING DI BANK SYARIAH MANDIRI (BSM) PERIODE 2008-2016 - Haryanto, Agung; Rahmatia, Diska (Ekonomi Islam, 2017)
The purpose of this study is to analyze the exchange rate, inflation, Gross Domestic Product (GDP), and the interest rate of commercial bank deposits on the amount of demand for foreign currency deposits in Bank Syariah Mandiri. The approach in this research is quantitative by using quarterly data from the year 2008 until 2016. The method of analysis in this research is Multiple Linear Regression which processed by using SPSS 20.0 and Microsoft Excel 2013 software. The result of the analysis shows that partially exchange rate, GDP, and the interest rate on deposits of commercial banks have an effect on foreign currency deposits, while the inflation variable has no effect. While simultaneously variables of the exchange rate, inflation, GDP, and interest rate of commercial bank deposit influence to foreign exchange deposit equal to 82,4%, and the rest 17,6% influenced by other variables not included in this research model.